A large arteriovenous fistula steals a considerable part of systemic blood flow during veno-arterial extracorporeal circulation support in a porcine model - Valerianova, A.; Mlcek, M.; Kittnar, O.; Grus, T.; Tejkl, L.; Lejsek, V.; Malik, J. (Frontiers in Physiology, 2023)
Background: Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is one of the most frequently used mechanical circulatory support devices. Distribution of extracorporeal membrane oxygenation flow depends (similarly as the cardiac output distribution) on regional vascular resistance. Arteriovenous fistulas (AVFs), used frequently as hemodialysis access, represent a low-resistant circuit which steals part of the systemic perfusion. We tested the hypothesis that the presence of a large Arteriovenous fistulas significantly changes organ perfusion during a partial and a full Veno-arterial extracorporeal membrane oxygenation support. Methods: The protocol was performed on domestic female pigs held under general anesthesia. Cannulas for Veno-arterial extracorporeal membrane oxygenation were inserted into femoral artery and vein. The Arteriovenous fistulas was created using another two high-diameter extracorporeal membrane oxygenation cannulas inserted in the contralateral femoral artery and vein. Catheters, flow probes, flow wires and other sensors were placed for continuous monitoring of haemodynamics and organ perfusion. A stepwise increase in extracorporeal membrane oxygenation flow was considered under beating heart and ventricular fibrillation (VF) with closed and opened Arteriovenous fistulas. Results: Opening of a large Arteriovenous fistulas (blood flow ranging from 1.1 to 2.2 L/min) resulted in decrease of effective systemic blood flow by 17%–30% (p < 0.01 for all steps). This led to a significant decrease of carotid artery flow (ranging from 13% to 25% after Arteriovenous fistulas opening) following VF and under partial extracorporeal membrane oxygenation support. Cerebral tissue oxygenation measured by near infrared spectroscopy also decreased significantly in all steps. These changes occurred even with maintained perfusion pressure. Changes in coronary artery flow were driven by changes in the native cardiac output. Conclusion: A large arteriovenous fistula can completely counteract Veno-arterial extracorporeal membrane oxygenation support unless maximal extracorporeal membrane oxygenation flow is applied. Cerebral blood flow and oxygenation are mainly compromised by the effect of the Arteriovenous fistulas. These effects could influence brain function in patients with Arteriovenous fistulas on Veno-arterial extracorporeal membrane oxygenation.